Eco de un baile (1998)
In the 1890's music composition in Colombia was still in the realm ofsocial dance music. A few interesting attempts were made in the field ofthe religious repertoire, opera and zarzuela. But, the waltz, the polka, themarch and the recently imported "danza" in the style of the Cuban habanera, reigned. On  August the 8th , 1891, an extraordinary dance was organized by a group of eight young men; a dance that was condemned by the Catholic Church for its luxurious expense. Jorge Pombo ( 1847-1912 ), a successful business man, poet and compositor wrote a set of waltzes for the occasion, Brisas del Funza, played in an orchestral version by 27 musicians, the night of the ball. We found the publisched piece (a version for the piano) in the archives of the Centro de Documentación Musical in Bogotá and were able lo glimpse at the late19th century society of Bogotá through the waltz and the ball it was written for.